The larval gut of Spodoptera frugiperda harbours culturable bacteria with metabolic versatility after insecticide exposure - Siddiqui, Junaid Ali; Fan, Ruidong; Liu, Yanjiang; Syed, Ali Hassan; Benlin, Yi; Chu, Qingshuai; Ding, Zeyang; Ghani, Muhammad Imran; Liu, Xuemi; Wakil, Waqas; Liu, Dong-Dong; Chen, Xiaoyulong; et al. (Insect molecular biology, 2025)
Spodoptera frugiperda (fall armyworm) poses a substantial risk to crops worldwide, resulting in considerable economic damage. The gut microbiota of insects plays crucial roles in digestion, nutrition, immunity, growth and, sometimes, the degradation of insecticides. The current study examines the effect of synthetic insecticides on the gut microbiome of third instar S. frugiperda larvae using both culture-dependent techniques and 16S rRNA gene sequencing for bacterial community profiling and diversity analysis. In untreated larvae, the sequencing approach revealed a diverse microbiome dominated by the phyla Firmicutes, Proteobacteria and Bacteroidota, with key genera including Bacteroides, Faecalibacterium and Pelomonas. In parallel, 323 bacterial strains were isolated and assigned to the orders Bacillales, Burkholderiales, Enterobacterales, Flavobacteriales, Lactobacillales, Micrococcales, Neisseriaies, Pseudomonadales, Sphingobacteriales and Xanthomonadales. The prevailing culturable species included Serratia marcescens, Klebsiella variicola and Enterobacter quasiroggenkampii. Treatment with sublethal concentrations of three insecticides (broflanilide, spinosad and indoxacarb) caused significant changes in gut microbiome diversity and composition. Treated larvae showed a shift towards increased Proteobacteria abundance and decreased Firmicutes. Specifically, Acinetobacter and Rhodococcus were dominant in treated samples. Functional predictions highlighted significant metabolic versatility involving nutrient processing, immune response, detoxification, xenobiotic metabolism, and stress response, suggesting microbial adaptation to insecticide exposure. Network correlation analysis highlighted disrupted microbial interactions and altered community structures under insecticide treatment. These findings enhance our understanding of how insecticides impact the gut microbiota in S. frugiperda and may inform future strategies for managing pest resistance through microbiome-based approaches.
Keywords: bacterial communities; microbial diversity; gut microbiome; pest management; RNA, Ribosomal, 16S; insect microbiome; insekticidy; synthetic insecticides; Bacteria; Gastrointestinal Microbiome; insecticide toxicity; střevní mikroflóra; larva; Spodoptera; Animals; zvířata; Insecticides; RNA ribozomální 16S; Larva; microbial interactions